Repeatability of stability parameters in herbaceous cotton - José Correia Farias, Francisco; Antônio Patto Ramalho, Magno; Paulo de Carvalho, Luiz; de Alencar Nunes Moreira, José; Nunes da Costa, Joaquim (Pesquisa Agropecuaria Brasileira, 1998)
Yield data of seed cotton from 56 experiments of cultivar evaluation were evaluated in the Northeast of Brazil, from 1985 to 1992, seeking to estimate the repeatability of stability parameters. Repeatability estimates for stability index (Pi), linear regression coefficient (β1) and determination coefficient (R2) were, most of them, from medium to high. The values ranged from 0.45 to 0.67 for the 1985 to 1990 period and 0.45 to 0.96 for 1991 to 1992. These results suggest that selection of these traits may give reasonable gains.